2019
DOI: 10.1111/jdv.16066
|View full text |Cite
|
Sign up to set email alerts
|

Review of non‐invasive vulvovaginal rejuvenation

Abstract: Vulvovaginal atrophy (VVA) or genitourinary syndrome of menopause (GSM) may affect up to 90% of menopausal women. Features include vulvovaginal atrophy, vulvovaginal laxity, vulvovaginal dryness and irritation, dyspareunia, anorgasmia and urinary symptoms. The vulva, vagina and bladder are oestrogen‐responsive tissues, but oestrogen replacement therapy is not possible in women who have hormone‐responsive cancers or normal oestrogen levels. Therefore, there is a role for alternative treatments. To date, three n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 83 publications
(360 reference statements)
0
38
0
Order By: Relevance
“…Although research on nonsurgical vaginal rejuvenation has increased greatly in recent years, there is still a lack of solid evidence that any energy-based device could effectively tighten the levator ani muscle. The main effect of energybased devices, including CO 2 lasers, are to induce the production and remodeling of collagen and elastin; they may also stimulate neovascularization (18). Histologically, biopsies after treatment revealed increased epithelial thickness, restoration of epithelial structures, and enhanced collagen deposition (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Although research on nonsurgical vaginal rejuvenation has increased greatly in recent years, there is still a lack of solid evidence that any energy-based device could effectively tighten the levator ani muscle. The main effect of energybased devices, including CO 2 lasers, are to induce the production and remodeling of collagen and elastin; they may also stimulate neovascularization (18). Histologically, biopsies after treatment revealed increased epithelial thickness, restoration of epithelial structures, and enhanced collagen deposition (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been reviewed for the efficacy and safety of the fractional CO 2 laser (23 case series, one randomized controlled trial [RCT], n=1179) and erbium:YAG laser (11 case series; n=692) in the treatment of VVA. 8 All studies were single center and none included a genuine placebo group. The authors concluded that the techniques appear to be safe with results persisting for up to 12 months, but highlighted the need for larger well-controlled studies.…”
Section: Clinical Overviewmentioning
confidence: 99%
“…The authors concluded that the techniques appear to be safe with results persisting for up to 12 months, but highlighted the need for larger well-controlled studies. 8 In the single RCT performed to date, the efficacy of fractional CO 2 laser, topical estriol, and combined (i.e., laser + estriol) treatment was compared in 45 postmenopausal women with VVA. 13 Based on VAS scores for dyspareunia, dryness, and burning, Vaginal Health Index scores, and Female Sexual Function Index scores, the authors concluded that CO 2 laser alone or in combination with topical estriol is a ‘good treatment option for VVA symptoms’, 13 although the conclusions were questioned due to methodological shortcomings and disparity between the reported results.…”
Section: Clinical Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Vulvovaginal atrophy and the genitourinary syndrome of menopause (VVA/GSM) affect the majority of women (48% of premenopausal and about 54–90% of postmenopausal women), often undermining quality of life (mainly due to vaginal dryness, dyspareunia and vaginal irritation). Photiou et al 4 . included 43 case series and one randomized controlled trial (RCT) in a review of the three main non‐surgical therapies (CO 2 laser, Erbium:YAG laser and radiofrequency treatment) for these conditions.…”
Section: The Latest On Non‐invasive Vulvovaginal Rejuvenationmentioning
confidence: 99%